Penerapan Project Based Learning Pada Mata Kuliah Matematika Diskrit Untuk Meningkatkan Kemampuan Pemecahan Masalah - Rifki Ristiawan; Noni Selvia; Nurfidah Dwitiyanti (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Learning that focuses on students' problem-solving abilities is the focus of higher education. Students who are able to develop critical thinking skills in solving problems are a necessity along with changes in workforce capability needs in the informatics era. One of the mathematics lessons at the higher education unit level is discrete mathematics. The problem that arises in discrete mathematics learning is that learning outcomes and the percentage of students completing lectures are still relatively low. The aim of this research is to improve students' solving abilities through the application of the project based learning method. This research uses classroom action research methods. The application of the project based learning method in discrete mathematics courses with graph material can improve students' abilities in solving mathematical problems, this can be seen from the research results after corrective actions were taken in learning activities in Cycles I and II. Based on the research results, it shows that through project-based learning, third semester RB class students in the Informatics Engineering Education Program at Indraprasta University PGRI Jakarta have improved their ability to solve mathematical problems in terms of individual grades and classical completion.